Zero-Energy Buildings - New Approaches and Technologies 2020
DOI: 10.5772/intechopen.93500
|View full text |Cite
|
Sign up to set email alerts
|

Solar Energy and Its Purpose in Net-Zero Energy Building

Abstract: The Net Zero Energy Building is generally described as an extremely energy-efficient building in which the residual electricity demand is provided by renewable energy. Solar power is also regarded to be the most readily available and usable form of renewable electricity produced at the building site. In contrast, energy conservation is viewed as an influential national for achieving a building’s net zero energy status. This chapter aims to show the value of the synergy between energy conservation and solar ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
0
16
1
Order By: Relevance
“…Research surveys have estimated that Tehran's sunny days and hours are about 313 days and 1742 hours a year, respectively. The increase from the southeast to the northwest of Iran is reduced, whereas it usually increases from the west to the east [22]. The irradiance map and statistical irradiance simulations show that irradiance level in clear air is theoretically high in Iran, including Yazd, Kerman, Tabas, Birjand, Iranshahr, Chabahar, Shiraz, Bam, Bushehr, and desert areas.…”
Section: Introductionmentioning
confidence: 94%
“…Research surveys have estimated that Tehran's sunny days and hours are about 313 days and 1742 hours a year, respectively. The increase from the southeast to the northwest of Iran is reduced, whereas it usually increases from the west to the east [22]. The irradiance map and statistical irradiance simulations show that irradiance level in clear air is theoretically high in Iran, including Yazd, Kerman, Tabas, Birjand, Iranshahr, Chabahar, Shiraz, Bam, Bushehr, and desert areas.…”
Section: Introductionmentioning
confidence: 94%
“…Net present value (NPV) is the difference between the present value of cash inflows and the present value of cash outflows over a period of time Net cash flow (NCF) is a metric that tells you whether or not greater cash got Figure 2. A floating solar power plant's components [9] here in or went out of a commercial enterprise inside a selected duration of time [44]. This balance is compared to interest rates as a predetermined criterion for project management.…”
Section: Net Present Valuementioning
confidence: 99%
“…High-potential photovoltaic technology has the potential to contribute to 5% of Europe's power needs by 2030 and 11% by 2050 [8]. However, just 1% of total electrical power required by humans, or 18,400 terawatts, is supplied by various solarto-electricity conversion systems [9].…”
mentioning
confidence: 99%
“…Concrete-based collectors the design and integration of SWH into building components such as the roof and walls have been finished. On an inclined roof, Esmaeili Shayan et al [10] studied and tested a concrete solar water heater (CSWH) for home hot water [8,9]. A researcher installed a solar concrete collector on a flat roof to restrict a home's heat absorption while still supplying domestic hot water [10].…”
Section: Greek Symbol Introductionmentioning
confidence: 99%
“…On an inclined roof, Esmaeili Shayan et al [10] studied and tested a concrete solar water heater (CSWH) for home hot water [8,9]. A researcher installed a solar concrete collector on a flat roof to restrict a home's heat absorption while still supplying domestic hot water [10]. The parametric analysis and experimental and numerical research of a CSWH as integrated on the wall and/or facade were reported by Azadbakht et al [11].…”
Section: Greek Symbol Introductionmentioning
confidence: 99%